2021
DOI: 10.3390/app11073038
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Dppz Derivatives and Their Interactions with DNA: Thirty Years and Counting

Abstract: Transition metal complexes with dppz-type ligands (dppz = dipyrido[3,2-a:2′,3′-c]phenazine) are extensively studied and attract a considerable amount of attention, becoming, from the very beginning and increasingly over time, a powerful tool for investigating the structure of the DNA helix. In particular, [Ru(bpy)2(dppz)]2+ and [Ru(phen)2(dppz)]2+ and their derivatives were extensively investigated as DNA light-switches. The purpose of this mini-review, which is not and could not be exhaustive, was to first in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 176 publications
(187 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the treated cells displayed a series of nuclear morphology changes including a smaller nuclear volume, condensed chromatin and an incomplete or fragmented nucleus, which correspond to the characteristic nuclear morphology of apoptosis. 26,27 It has been known that the intercalation of an intercalator between the adjacent base-pairs of DNA results in a substantial conformation change in the regular helical structure of DNA, characterized by the despiralization of DNA and the extension of its helix, 28,29 which inhibits DNA replication either by stabilizing the cleaved DNA produced with topoisomerase II, or by preventing DNA-binding of topoisomerase I, and leads to cell death. 30,31 Generally, the DNA affinity of a drug is positively consistent with its cytotoxic potency.…”
Section: Assessment Of Nuclear Damagementioning
confidence: 99%
“…Furthermore, the treated cells displayed a series of nuclear morphology changes including a smaller nuclear volume, condensed chromatin and an incomplete or fragmented nucleus, which correspond to the characteristic nuclear morphology of apoptosis. 26,27 It has been known that the intercalation of an intercalator between the adjacent base-pairs of DNA results in a substantial conformation change in the regular helical structure of DNA, characterized by the despiralization of DNA and the extension of its helix, 28,29 which inhibits DNA replication either by stabilizing the cleaved DNA produced with topoisomerase II, or by preventing DNA-binding of topoisomerase I, and leads to cell death. 30,31 Generally, the DNA affinity of a drug is positively consistent with its cytotoxic potency.…”
Section: Assessment Of Nuclear Damagementioning
confidence: 99%
“…The most famous compounds triggering the interest of ruthenium(II) polypyridyl complexes as powerful tools to study DNA are the [Ru(bpy) 2 ( dppz )] 2+ and [Ru(phen) 2 ( dppz )] 2+ (dppz = dipyrido[3,2- a :2′,3′- c ]phenazine) complexes [ 188 ]. These complexes are called light-up probes as they are not luminescent in water but do emit brightly in DNA containing aqueous solutions.…”
Section: Interactions Of Ruthenium(ii) Complexes With G-quadruplexesmentioning
confidence: 99%
“…Diverse types of tailored polypyridyl ligands bearing various substituents have extensively been studied for a range of applications, such as the modeling of photosystems, luminescent probes for deoxyribonucleic acid (DNA), ribonucleic acid or Gquadruplexes, etc. 1,2 Recently, spectroelectrochemical studies of the complex [Ru(tap) 2 (dppz)] 2+ (tap = 1,4,5,8-tetraazaphenanthrene, dppz = dipyrido[3,2-a:2′,3′-c]phenazine) have revealed that the singly reduced cationic species can be generated via a photoelectron transfer from guanine (G) rather than a predicted proton-coupled electron transfer (Scheme 1). The infrared (IR) spectral changes accompanying the formation of the 1e − reduced species were revealed by spectroelectrochemistry.…”
Section: ■ Introductionmentioning
confidence: 99%